Teaching the Russian Language in Online Courses - Eshkuvatova, Mokhira Amanturdievna (PT. Antis International Publisher, 2024)
This article provides information on the introduction of online courses to the educational process, and the identification of positive and negative aspects of education. The importance and value of online education in the conditions of Uzbekistan is analyzed. As with everything, online education has its pros and cons.